Electronic structures at the interface between LiNbO3 and the metal electrodes: first-principles calculation. Issue 1 (10th December 2021) - Wang, Hao; Liao, Yunxia; Liu, Yue; Li, Yanshuai; Yang, Lin; Wei, Xianggang; Shang, Wenlong; Ye, Kun; Hou, Wenjing
Abstract: In this paper, iterative optimization is carried out within the allowable range of mismatch of the crystal lattice, and the density of states, energy band, differential charge density and effective mass of the cell-electrode interface are calculated and analyzed. It is proposed to improve the application of ferroelectric LiNbO3 -based electric-optic modulators with a better choice of electrodes, and can provide a carrier-transfer basis for the ferroelectric materials. And the calculation of the interface offered selection for the new materials electrode, to improve the efficiency in the electric-optic transfer and the storage efficiency in the future.